The Effect of Employee Empowerment and Job Satisfaction on Turnover Intention with Organizational Commmitment as Intervening in the Land Office in DKI Jakarta Province - Restu Istiningdyah; Andreas Wahyu Gunawan P (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of employee empowerment and job satisfaction on turnover intention mediated by organizational commitment. The data used in this study is primary data sourced from the results of the questionnaire collection. The research sample was selected using purposive sampling of as many as 203 respondents. Data analysis in hypothesis testing using AMOS and Sobel Test programs. The results showed that there was a positive effect of employee empowerment and job satisfaction on organizational commitment. In addition, employee empowerment, job satisfaction, and organizational commitment have a negative relationship to turnover intention. The results also show that organizational commitment can be an intervening variable between employee empowerment and job satisfaction variables on turnover intention. The results of the study provide information that the higher the employee empowerment, job satisfaction, and organizational commitment of employees will reduce the desire to leave the organization (turnover intention).